A hybrid approach for quantitative assessment of construction projects risks: The case study of poor quality concrete. (May 2019) - Nasirzadeh, Farnad; Ghasem Kashi, Mohammad; Khanzadi, Mostafa; Carmichael, David G.; Akbarnezhad, Ali
Highlights: A new fuzzy-based approach is presented for quantitative assessment of project risks. The probability of risk is assessed by decomposing into root causes prompting it. The impact of risk is assessed by modeling possible scenarios arising from it. Finally, the severity of risk is determined as a fuzzy number. Using the proposed method, the risk assessment is done for the poor quality concrete. Abstract: This research presents a new fuzzy-based approach for quantitative assessment of construction projects risks. Using the proposed approach, the risk is decomposed into internal and external root causes prompting it and the probability of occurrence of risk is assessed by fault tree analysis (FTA). The impact of identified risks is then assessed by event tree analysis (ETA) considering the possible negative scenarios arising from the occurrence of a risk. Owing to the imprecise and uncertain nature of various factors affecting the probability and impact of identified risks, fuzzy logic is integrated into the proposed FTA and ETA methodologies. Finally, the severity of risk is assessed in the form of a fuzzy number using the proposed integrated fuzzy FTA-ETA approach. To evaluate the performance of the proposed method, it is implemented in a large building project and the quantitative risk assessment is done for the "poor quality concrete" as one of the most significant identified risks.